y-53/6=4

Simple and best practice solution for y-53/6=4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y-53/6=4 equation:



y-53/6=4
We move all terms to the left:
y-53/6-(4)=0
determiningTheFunctionDomain y-4-53/6=0
We multiply all the terms by the denominator
y*6-53-4*6=0
We add all the numbers together, and all the variables
y*6-77=0
Wy multiply elements
6y-77=0
We move all terms containing y to the left, all other terms to the right
6y=77
y=77/6
y=12+5/6

See similar equations:

| (a/7)-4=2 | | 6x-12-4x-17=-4 | | 3x+20+7x-40=180 | | 8(y-92)=64 | | f/2=10 | | 6(w-72)=72 | | 3(f-77)=27 | | g/6=-2 | | 58=-y/4 | | 5=k-2=11 | | -3(7-6x)=-93 | | z=3/4=5 | | 16^2p-3*4^-2p=2^4 | | m+(-23)=46 | | 7x-8x=3×5+2 | | x+38=8 | | -7-6x=-1-3x | | 2×+5z=33 | | -7(1+2y)-2y=-13 | | 30=-y/2 | | 3×+2z=22 | | x+5=5+6x | | .65x=39 | | 38=w/4+13 | | 180=(9x-5)+(14x-91) | | 5u+13=108 | | 5n^2+11n-9718=0 | | 4x+18=5x/2 | | 30=4y-14 | | 6•16x-1=90 | | 21=y/3-10 | | 216=36^4-x |

Equations solver categories